Revealing the Spectral Properties of Magnetic Turbulence by Synchrotron Polarization Gradients - Jian-Fu Zhang; Zi-Qi Liu (The Astrophysical Journal)
Based on the modern understanding of MHD turbulence theory, we propose a new method for measuring the spectral properties of magnetic turbulence by synchrotron polarization gradient analysis. Using synthetic polarization observational data, we first confirm the feasibility of the gradient technique to determine the scaling properties of magnetic turbulence. We then apply this technique to the Galactic plane survey data from the Australia Telescope Compact Array and obtain the power-law spectral feature of the Galactic magnetic turbulence of E  ∝  k ^−10/3 . Gradient techniques open up a new way to obtain spectral properties of magnetic turbulence from polarization observations, such as the Low-Frequency Array for Radio Astronomy, in the presence of low-frequency and strong Faraday depolarization.